KEGIATAN YOGA TAWA BAGI LANSIA DI BANJAR BELALUAN SEBAGAI UPAYA MENJAGA KESEHATAN PADA USIA LANSIA - I Putu Yoga Darmaika; Komang Ani Tri Agustini; I Nyoman Bagus Satria Wiguna; Yohana Alfrida Inna; Firdon Ngailo; I Gusti Ayu Rai; Ni Luh Putu Indrawathi (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
The elderly are an age group vulnerable to physical, psychological, and social decline due to the aging process. Among the common problems experienced by the elderly are decreased physical fitness, increased stress levels, and reduced social interaction, which can impact their quality of life. In Banjar Belaluan, recreational health activities appropriate to the elderly's needs are still limited. Therefore, this community service activity aims to improve the physical, mental, and social health of the elderly through laughter yoga. This activity involved 35 elderly people who participated in laughter yoga sessions regularly twice a week. The implementation method consisted of socialization, laughter yoga practice, and evaluation. Data were obtained through direct observation and informal interviews, then analyzed descriptively and qualitatively. The results showed that laughter yoga had a positive impact on participants, characterized by increased enthusiasm, improved mood, reduced anxiety, and increased social interaction among the elderly. Furthermore, participants felt more relaxed and comfortable after participating. Thus, laughter yoga can be an effective alternative promotional and preventive activity to help maintain the health and improve the quality of life of the elderly in the community.